Preparation Scheme of Active Pt/SiC Catalyst and Its Phase Changes During Sulfuric Acid Decomposition to Produce Hydrogen in the SI Cycle - Khan, Hassnain Abbas; Jung, Kwang-Deog (SPRINGER, 2017)
The Pt/SiC-AP catalyst is prepared by the polyol method using acid treated SiC for sulfuric acid (SA) decomposition, which exhibits the highest activity and stability among the Pt/SiC catalysts prepared by four different methods. In a longer-term stability test at 850 A degrees C and a GHSV of 53,500 mL/g(cat)/h for 30 h, the Pt/SiC-AP catalyst shows the SA conversion of 82%. The activity loss of the Pt/SiC-AP catalyst is observed at 15 h, but the catalyst is almost stabilized at the SA conversion of ca. 78% afterwards. The Pt loss with the Pt/SiC-AP catalyst is the least among the prepared catalysts. Most of Pt loss with the Pt/SiC-AP catalyst occurs within 5 h during the phase change from Pt/SiC to Pt/SixCyOz/SiC and the Pt loss is rarely observed for 30 h thereafter. The acid treatment of the SiC support improves the catalytic stability by enhancing the interaction between Pt and SiC and the Pt/SiC catalyst with well-dispersed Pt particles is obtained by using the polyol method. [GRAPHICS] .
Keywords: WATER-SPLITTING CYCLES; OXYGEN-GENERATING REACTION; DURABILITY; INTERFACES; OXIDATION; CARBIDE; H2SO4; ARXPS; STEP; SO2